PENANGANAN KASUS TINDAK PIDANA PADA MASA PANDEMI COVID-19 DALAM HUBUNGANNYA DENGAN PENERAPAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA (KUHAP) - H.M. Juliadi Razali (Universitas Suryakancana, 2021)
Coronavirus Disease 2019 (Covid-19) is a new type of disease that has never been previously identified in humans. WHO declared Covid-19 a global pandemic. The Covid-19 pandemic has created a domino effect in many areas of people's lives. The impact of the Covid-19 pandemic has also caused problems in handling criminal cases starting from the process of investigation, prosecution, to trial because they have to follow the Health Protocol and cannot be done face-to-face (direct contact), even the trial process is carried out in person. virtual. This of course deviates from the process of handling criminal cases adopted by the Criminal Procedure Code because the Criminal Procedure Code does not regulate the instructions for conducting virtual trials. The implementation of a virtual trial, in reality, creates various obstacles. In terms of facilities, many courtrooms have not been arranged with teleconferencing facilities. Many internet networks are also unstable. The lack of resources that know the field of mastery of information technology. On the other hand, the probability of a trial hacking is very high. On the suspect/defendant side, the obstacles that occur include the validity of the evidence in the trial and obstacles to the evidentiary process involving many witnesses and also the physical evidence presented in the evidentiary process. In addition, the fulfillment of the suspect's rights also encountered obstacles, where the defendant and his legal advisor were not allowed to consult directly in a virtual trial.Â Keywords : Case Handling, Crime, Covid-19 Pandemic, Criminal Procedure Code.Â